2020
DOI: 10.2196/14679
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on the Usefulness of an Artificial Intelligence–Assisted Symptom Checker: Cross-Sectional Survey Study

Abstract: Background Patients are increasingly seeking Web-based symptom checkers to obtain diagnoses. However, little is known about the characteristics of the patients who use these resources, their rationale for use, and whether they find them accurate and useful. Objective The study aimed to examine patients’ experiences using an artificial intelligence (AI)–assisted online symptom checker. Methods An online surve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
137
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(142 citation statements)
references
References 28 publications
3
137
0
2
Order By: Relevance
“…Studies of other symptom checkers also report a high degree of perceived utility. In a convenience sample of 304 US users of the Isabel symptom checker, 90.1% (274/304) agreed or strongly agreed that it gave them useful information, and a similar proportion said they would use the tool again [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of other symptom checkers also report a high degree of perceived utility. In a convenience sample of 304 US users of the Isabel symptom checker, 90.1% (274/304) agreed or strongly agreed that it gave them useful information, and a similar proportion said they would use the tool again [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of reducing the burden on primary care, some 12.8% (63/494) of respondents in this study predicted that they would have used a less urgent care option such as a pharmacist or self-care had they used Ada before visiting the doctor. It remains to be seen how many patients would actually follow advice on where to go next, but in the survey of US Isabel symptom checker users, about half (14/26, 54%) of those advised to go to the emergency department reported that they did so [ 29 ]. Another recent paper reported broadly similar findings from over 150,000 encounters with the Buoy Health symptom checker: 18.8% of patients who had planned to visit primary care reduced the urgency of care they would seek, and 2.6% increased the urgency of their intended level of care [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In assessing symptom checker benefits, it is important to understand user perspectives on the platform after actual use rather than simply assessing their accuracy in fictitious situations [ 14 , 15 ]. A study that examined patients’ experiences using the symptom checker “Isabel” found that the platform was most commonly used to better understand the causes of symptoms, followed by deciding whether or not to seek care [ 14 ]. Most of the patients in that study (274/304, 90.1%) reported receiving useful information for their health problems and reported that they would use the symptom checker again (278/304, 91.4%) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study that examined patients’ experiences using the symptom checker “Isabel” found that the platform was most commonly used to better understand the causes of symptoms, followed by deciding whether or not to seek care [ 14 ]. Most of the patients in that study (274/304, 90.1%) reported receiving useful information for their health problems and reported that they would use the symptom checker again (278/304, 91.4%) [ 14 ]. These findings are in line with another study that examined perspectives on use of the “Ada” symptom checker, which showed that most of the participants (443/503, 88.1%) would recommend the platform to a relative [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…People see value in symptom checkers, but while self‐reported outcomes are important, they are not necessarily associated with safety or improved health service efficiency.…”
Section: Should We Be Integrating Online Symptom Checkers Into Clinicmentioning
confidence: 99%